Penerapan Model Pembelajaran Berbasis Masalah Dalam Meningkatkan Hasil Belajar Bahasa Indonesia Dikelas IV SD Negeri 1 Nanasi - Hamber, Atalya Cherin Dwi; Rindengan, Mersty E.; Dien, Stien A. (Peneliti.net, 2023)
Based on the results of research carried out in class IV of SD Negeri 1 Nanasi with a total of 13 students consisting of 7 male students and 6 female students. This was done to determine the feasibility of the Problem Based Learning model in learning Indonesian for class IV students at SD Negeri 1 Nanasi. The aim of this classroom action research is to analyze and improve the Indonesian language learning process on poetry reading material using the Problem Based Learning model in class IV of SD Negeri 1 Nanasi. Problem Based Learning is a model in the learning approach process that presents problems that are realistic and meaningful for students to learn in their learning environment about critical thinking, problem solving skills, gaining essential knowledge and concepts from the subject matter being studied. This research uses the classroom action research (PTK) method, according to Arikunto (2010: 16) with four stages, namely: planning, implementation, observation and reflection used in cycles I and II. Student learning outcomes in cycle I received an average score of 60 and the percentage of student learning completeness was 30 with the Incomplete criteria and increased in cycle II with the average student score being 82 and the percentage of learning completeness reaching 92 with the complete criteri